AB0898 Automated Determination of Bone AGE and Bone Mineral Density in Patients with Juvenile Idiopathic Arthritis. (10th June 2014) - Anink, J.; Nusman, C.M.; van Suijlekom-Smit, L.W.; van Rijn, R.R.; Maas, M.; van Rossum, M.A.
Abstract : Background: Chronic inflammation combined with glucocorticoid treatment and immobilization put juvenile idiopathic arthritis (JIA) patients at risk of impaired growth and reduced bone mineral density (BMD). Conventional methods for evaluating bone age and BMD (such as manual evaluation using the Greulich and Pyle atlas and Dual-energy X-ray densitometry (DXA)) are time consuming, or come with high costs and additional radiation exposure. Objectives: To evaluate feasibility and reproducibility of an automated method for determination of bone age and (cortical) bone mineral density (cBMD) in severely affected juvenile idiopathic arthritis (JIA) patients. A secondary objective was to describe bone age and cBMD in this specific JIA population, eligible for biologic treatment. Methods: Prospectively included patients from two centres participating in the Dutch Arthritis and Biologicals in Children (ABC) Register between 1999 en 2012 were eligible for this study. Sixty-nine patients with standard hand radiographs at start of etanercept and calendar age within the reliability ranges of the programme (2.5-17 years for boys and 2-15 years for girls) were included. Radiographs were analysed with the BoneXpert method, automatically determining bone age and cBMD expressed as bone health index (BHI).[1] Bone age and BHI were expressed as absolute values, compared with reference values from a healthy population and subsequently expressed as Z-scores. Agreement between two measurements (reproducibility) and between left and right hand was assessed with the intraclass correlation coefficient (ICC). Regression analysis was used to identify variables associated with Z-scores of BHI. Results: BoneXpert reliably evaluated radiographs of 67 patients (radiographs of two patients were rejected due to poor image quality). Agreement between repeated measurements (ICC 0.999-1.000) and left-right hand radiographs (ICC 0.838-0.996) was good. Mean Z-scores of bone age (-0.36, p=0.051) and BHI (-0.85, p<0.001) were lower compared with the healthy population. Male gender was associated with a lower Z-score of BHI (0.65 SD, p=0.021). Conclusions: BoneXpert is an easy to use and reproducible method for assessing bone age and cBMD in patients with JIA, provided that radiographs are of reasonable quality and patients' bone age lies within the age ranges of the program. The population investigated had delayed bone maturation and lower cBMD compared with healthy children. References: Thodberg HH, van Rijn RR, Tanaka T, Martin DD, Kreiborg S. A paediatric bone index derived by automated radiogrammetry. Osteoporos Int. 2010 Aug; 21(8):1391-1400. Acknowledgements: The authors wish to acknowledge Hans Henrik Thodberg for his support with and the free use of BoneXpert. Disclosure of Interest: J. Anink: None declared, C. Nusman: None declared, L. van Suijlekom-Smit Grant/research support: For the submitted work: Dutch Board of health insurances, Pfizer and Abbvie, R. van Rijn: None declared, M. Maas: None declared, M. van Rossum: None declared DOI: 10.1136/annrheumdis-2014-eular.3129